Physical activity in type II diabetes - Kępczyk, Martyna; Kościołek, Aleksandra; Kłak, Igor; Czekaj, Oliwia; Demianenko, Yehor; Kościołek, Dawid; Misiak, Jakub; Urbaś, Michał; Ojdana, Miłosz; Surowiecka, Kaja (Journal of Education, Health and Sport, 2024)
INTRODUCTION AND AIM OF WORK A factor significantly influencing the risk of lifestyle diseases, including diabetes, is physical activity. The last decades have been characterized by reduced physical activity in developed countries. This is associated with deteriorating population health and the risk of developing type 2 diabetes. Appropriately tailored physical effort is essential for the proper functioning of the body. MATERIALS AND METHODS The aim of the study is to compare the physical activity levels among individuals with diabetes. To achieve this goal, a survey was created and subsequently distributed via social media (Telegram platform) in August 2023. RESULTS A total of 101 surveys were collected, with the average age of respondents being 34 years old. Among the respondents, 25 individuals (24.75%) had diabetes, while the rest did not have the condition. Out of the participants, 46 respondents indicated a family history of diabetes. Diabetes was statistically significantly associated with a family history of diabetes (p=0.037). Furthermore, the diabetes group exhibited a higher frequency of overweight and obesity (p=0.027). The respondents’ body weight was positively correlated with both the frequency of food intake (r=0.31, p=0.011) and negatively correlated with the frequency of exercise (r= -0.22, p=0.046). CONCLUSIONS The gathered results confirm the familial nature of diabetes occurrence. They also highlight the significant role of exercise in maintaining body weight, as well as the importance of diet.